2005
DOI: 10.1111/j.1442-2042.2005.01145.x
|View full text |Cite
|
Sign up to set email alerts
|

Antiandrogenic therapy can cause coronary arterial disease

Abstract: Aim : To study the change of lipid metabolism by antiandrogen therapy in patients with prostate cancer. Materials and methods : We studied with a 2.5 years follow-up the changes in plasma cholesterols (C), triglycerides (TG), lipoproteins (LP), and apolipoproteins (Apo) B-100, A-I, and A-II profiles in 24 patients of mean age 60 years with low risk prostate cancer (stage: T1cN 0 M 0 , Gleason score: 2-5) during treatment with cyproterone acetate (CPA) without surgical management or radiation therapy.Results : … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Similar findings were observed by Smith et al 21 and Nishiyama et al 22 Smith et al 23 reported that ADT for CaP using GnRH agonist treatment of a period of months resulted in significantly increased triglyceride levels. Chen et al 24 reported that ADT for 2.5 years resulted in significantly increased triglyceride and decreased HDL cholesterol values; however, only HDLC3 was affected. Another prospective study of 40 men who received ADT for a year showed a 9% increase in total cholesterol, 7.3% in LDL cholesterol, and 26.5% in triglyceride levels.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were observed by Smith et al 21 and Nishiyama et al 22 Smith et al 23 reported that ADT for CaP using GnRH agonist treatment of a period of months resulted in significantly increased triglyceride levels. Chen et al 24 reported that ADT for 2.5 years resulted in significantly increased triglyceride and decreased HDL cholesterol values; however, only HDLC3 was affected. Another prospective study of 40 men who received ADT for a year showed a 9% increase in total cholesterol, 7.3% in LDL cholesterol, and 26.5% in triglyceride levels.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al studied changes in plasma cholesterols, lipoproteins, and apolipoproteins (Apo) B-100, A-I, and A-II profiles over 2.5 years. They found significant decreases of HDL-C, Apo A-I and Apo A-II and an increase of triglyceride levels and VLDL associated with ADT [55]. In the same study, Apo B-100 levels were not statistically different between ADT and control group.…”
Section: Adt and Dyslipidemiamentioning
confidence: 83%
“…It has been shown consistently in various studies that ADT increase total cholesterol level. Some studies also showed increases in triglyceride level [28, 54, 55] versus others, which did not show significant elevations in triglyceride level in the ADT group [25, 26, 53]. Although total cholesterol was often increased during ADT therapy, HDL-C also found to increase in some studies, which might decrease the adverse consequence of increased total cholesterol.…”
Section: Adt and Dyslipidemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, studies have demonstrated that ADT is associated with dyslipidemias, lower levels of high density lipoprotein and higher levels of triglycerides, total cholesterol and low density lipoprotein concentrations. Furthermore, Chen et al [19] revealed that long-term ADT (mean duration: 2.5 years) significantly decreased the levels of apolipoproteins I and II. Lastly, Nishiyama et al [20] demonstrated that after 6 months of ADT, body weight, levels of fasting blood sugar, serum total cholesterol, blood urea nitrogen, compensated calcium, inorganic phosphorus, bone-specific alkaline phosphatase, and compensated urinary deoxypyridinoline increased significantly.…”
Section: Discussionmentioning
confidence: 99%